2015
DOI: 10.1136/neurintsurg-2015-012101
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four different collateral scores in acute ischemic stroke by CT angiography

Abstract: Compared with the Christoforidis and Miteff scores, the modified ASITN/SIR and ASPECTS collateral scores showed consistently higher correlation with the extent of early infarct core and mismatch volume. This is probably because these scores evaluate the extent and delay of vascular enhancement in the affected territory rather than the backflow of contrast medium to the occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 30 publications
3
52
0
1
Order By: Relevance
“…Various perfusion parameters in both CT and MRI have been studied (Lansberg et al., ; Mundiyanapurath et al., ; Seker et al., ; Straka et al., ). Mokin et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various perfusion parameters in both CT and MRI have been studied (Lansberg et al., ; Mundiyanapurath et al., ; Seker et al., ; Straka et al., ). Mokin et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that infarct core correlates well with collaterals and final infarct volume in anterior circulation stroke (Lee et al., ; Mokin et al., ; Seker, Potreck, Möhlenbruch, Bendszus, & Pham, ). The correlation of various T max volumes with clinical outcome, however, is not clear yet.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, the Miteff collateral grades, or a modified version of the Christoforidis collateral grading system 33 for dynamic CTA, were not significantly linearly correlated with the infarct core volume and the mismatch ratio. 42 …”
Section: Imaging Methods and Grading Criteria For Cerebral Collateralmentioning
confidence: 99%